hw06su10_soln - ECE 2025 Summer 2010, Problem Set 6,...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ECE 2025 Summer 2010, Problem Set 6, Solutions 6.1 We are given a system function that simplifies according to H ( z ) = z- 2 ( 1- z- 1 )( 1 + j 5 z- 1 )( 1- j 5 z- 1 ) = z- 2 ( 1- z- 1 )( 1 + 25 z- 2 ) = z- 2 ( 1- z- 1 + 25 z- 2- 25 z- 3 ) = z- 2- z- 3 + 25 z- 4- 25 z- 5 (a) The difference equation is obtained by taking the inverse z-transform of the input-output relation Y ( z ) = ( z- 2- z- 3 + 25 z- 4- 25 z- 5 ) X ( z ) which yields y [ n ] = x [ n- 2]- x [ n- 3] + 25 x [ n- 4]- 25 x [ n- 5] (b) The impulse response is obtained by taking the inverse z-transform of the system function H ( z ) = z- 2- z- 3 + 25 z- 4- 25 z- 5 which yields h [ n ] = [ n- 2]- [ n- 3] + 25 [ n- 4]- 25 [ n- 5] (c) The z-transform of the input signal x [ n ] = [ n ] + 2 [ n- 1] + 3 [ n- 2] + 2 [ n- 3] + [ n- 4] is given by X ( z ) = 1 + 2 z- 1 + 3 z- 2 + 2 z- 3 + z- 4 so the output signal is obtained by taking the inverse z-transform of Y ( z ) = ( z- 2- z- 3 + 25 z- 4- 25 z- 5 )( 1 + 2 z- 1 + 3 z- 2 + 2 z- 3 + z- 4 ) = z- 2 + z- 3 + 26 z- 4 + 24 z- 5 + 24 z- 6- 26 z- 7- 25 z- 8- 25 z- 9 which yields y [ n ] = [ n- 2]+ [ n- 3]+26 [ n- 4]+24 [ n- 5]+24 [ n- 6]- 26 [ n- 7]- 25 [ n- 8]- 25 [ n- 9] (d) The system function is equal to H ( z ) = z- 2 ( 1- z- 1 )( 1 + j 5 z- 1 )( 1- j 5 z- 1 ) The zeros of the system are located at points in the z-plane at which H ( z ) = 0. In this case, there are three zeros located at z = 1 , j 5, and only the zero located at z = 1 is on the unit circle (at angle = 0). Consequently, the only frequency which would be nulled by this system is = 0 (and the corresponding alias frequencies = 2 , 4 ,... ). This can also be determined by evaluating the frequency response function H ( e j ) = e- j 2 ( 1- e- j )( 1 + j 5 e- j )( 1- j 5 e- j ) where the second factor vanishes at = 0....
View Full Document

This note was uploaded on 10/21/2010 for the course ECE 2025 taught by Professor Juang during the Summer '08 term at Georgia Institute of Technology.

Page1 / 8

hw06su10_soln - ECE 2025 Summer 2010, Problem Set 6,...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online